International Student Mobility in the United States - Farrugia, Christine; Villarreal, Ashley (International Higher Education, 2013)
The number of globally mobile students has nearly doubled over the past ten years, from 2.1 million students in 2001 to 4.1 million students in 2011. According to Open Doors 2012: Report on International Educational Exchange, the U.S. hosted 764,795 international students in 2011/12, an increase of 3.7 percent from the previous year. International students in the U.S. now make up 19 percent of the world's globally mobile students, and as university campus enrollments grow, so does the proportion of students enrolling in them from abroad. The number of U.S. students studying abroad reached 273,996 in 2010/11, an increase of 1.3 percent over the prior year and an increase of 78 percent over the past ten years.